Measuring Option Implied Degree of Distress in the US Financial Sector Using the Entropy Principle - Philipp Matros; Johannes Vilsmeier (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2012)
We estimate time series of option implied Probabilities of Default (PoDs) for 19 major US financial institutions from 2002 to 2012. These PoDs are estimated as mass points of entropy based risk neutral densities and subsequently corrected for maturity dependence. The ob- tained time series are evaluated with regard to their consistency and predictive power and their properties are compared to Credit Default Swap Spreads (CDS). Moreover, we also derive an indicator for the systemic risk in the US nancial sector. We find that the PoDs are superior to CDS in identifying the high risk banks prior to the Lehman crisis.
Keywords: C14; C32; G01; G21; 330; Entropy Principle; Risk Neutral Density; Probability of Default; Financial Stability Indicator; Credit Default Swaps; Finanzmarktkrise; Bankenkrise; Bankinsolvenz; Statistische Verteilung; Entropie; Finanzsektor; USA